CAUSES OF COLLUSION AMONG PEOPLE IN CONSTRUCTION - Ayodeji OKE; Clinton AIGVABOA; Zacharia Mangena; Wellington THWALA (Journal of Construction Project Management and Innovation)
Collusion is an unethical and disreputable agreement among parties of similar interests, with the intention of achieving a goal through immoral and dishonest means. Proper ethical procurement practice in the construction industry will enable the Construction Industry Development Board (cidb) to achieve their mandate, which is to promote uniformity in construction procurement, efficient and effective infrastructure delivery, and development of emerging contractors, including transformation. It will also enable the Competition Commission of South Africa (CCSA) to achieve their mandate, which is fair competition in all industries. With collusion occurring, it will be difficult for the cidb and the CCSA to achieve their mandate. This study examined the influences of this practice among competitors and stakeholders in the construction industry. Various causal factors of collusion among parties were extracted from a review of existing and relevant literature, and they were further evaluated to arrive at the specific ones that are relevant to the construction industry and the selected area of study. Using these factors, closed-ended questionnaires were prepared and administered to construction stakeholders with an adequate level of experience in the construction industry. The number of questionnaires distributed was 50, of which 45 were returned. Five of the questionnaires were not correctly and completely filled out. The distribution method used was self-administration. In addition, purposive sampling was used. The findings from the 40 respondents indicate that the major cause of collusion in the construction industry is greed of various stakeholders that are tasked with the responsibility of managing and monitoring construction contracts and activities, particularly the contractors. Political influence, among other factors, was also identified as a major reason for collusion. Empowering emerging contractors, a well-regulated environment, fair competition, and improving procurement management are the most important solutions that can prevent collusion from occurring. Furthermore, good ethical practice is one of the solutions that professionals should adopt. In view of this, agencies, institutes, and boards concerned with the monitoring and regulation of professionals, contractors, and general construction activities should therefore ensure that appropriate sanctions and punishments are applied for any members found culpable.